A review of the development of environmental impact assessment legislation in selected African countries - Mubangizi, John Cantius (Department of Electrical Engineering, 2021)
Legislation by its nature is a dynamic process. In order to keep abreast with changing circumstances and demands, new legislation often has to be introduced and old legislation amended. Recent global developments have led to widespread environmental awareness and the need for better methods of environmental protection. As a result there have been remarkable developments in the field of environmental law during the last two or three decades. Environmental Impact Assessment legislation is one area in which changes have been quite profound. This study takes into account such changes and it is for this reason that I have to point out that the information contained in this study is valid as at the end of August 1994.